Motor deficits in youth with concussion history: Issues with task novelty or task demand? - Dalecki, M.; Usand, J.; Van Gemmert, A. W. A.; Sergio, L. E. (International Journal of Sports Medicine, 2020)
The present study expands previous work on eye-hand decoupling deficits in youth with concussion history. It examines whether deficits can be linked to difficulties adapting to new task constraints or meeting ongoing task demands. Data from 59 youth with concussion history (M=11 months post-concussion) and 55 no history controls were analyzed. All 114 participants (M=12.5 yrs.) performed two touchscreen-based eye-hand coordination tasks: A standard task with vision and motor action in alignment, and an eye-hand decoupling task with both spatially decoupled, with twenty trials per task condition. First (trial 1-4), middle (trial 9-12), and last (trial 17-20) trial blocks were analyzed in each condition across groups, as well as first and last blocks only. The latter analysis showed in the first block longer response times in the concussion history group in the eye-hand decoupling condition due to a general slowdown of the reaction times across blocks and a trend for higher movement times. Our findings suggest that youth with concussion history have difficulty to adapt to new task constraints associated with complex skill performance during a short series of trials. These results are relevant for athletic trainers, therapists and coaches who work with youth with concussion history.